Reengineering of administrative processes in the institutions providing health services (IPS) of the Colombian Caribbean Region (2017)
At present, 146 IPS located in the Colombian Caribbean Region have a financial deficit and deep administrative failures that prevent their competitiveness in the market. Hence, these institutions must incorporate an effective tool that allows them to restructure their processes and bring them to the achievement of their objectives. The present study of investigation is directed, precisely to verify if these entities have the conditions and the knowledge to incorporate the managerial tool of reengineered with aim to improve its administrative processes.